Compact objects from gravitational collapse: an analytical toy model - Malafarina, D.; Joshi, Pankaj S. (My University, 2015)
We develop here a procedure to obtain regular static configurations as resulting from dynamical gravitational collapse of a massive matter cloud in general relativity. Under certain general physical assumptions for the collapsing cloud, we find the class of dynamical models that lead to an equilib-rium configuration. To illustrate this, we provide a class of perfect fluid collapse models that lead to a static constant density object as limit. We suggest that similar models might possibly constitutethe basis for the description of formation of compact objects in nature.
Keywords: gravitational collapse; black holes; compact objects